Návrh plánu údržbářských prací práškového granulačního kotle - Lipus, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Diplomová práce se zabývá problematikou aplikace metody RCM (Reliability Centered Maintenance) na velká energetická zařízení (kotle a jejich příslušenství) s využitím softwarového nástroje AMST společnosti SKF v podmínkách konkrétní energetické společnosti.

The diploma thesis deals with the issues concerning implementation of the RCM (Reliability Centred Maintenance) method on large power installations (boilers and their accessories) with the use of the new AMST software tool in the conditions of a particular energy company.
The Draft Plan of Maintenance Work on Powder Granulation Boiler
Keywords: Disponibilita; údržba; elektrárna; kotel; příčina poruchy; mód poruchy; náklady na údržbu; standard údržby; matice kritičnosti.; Availability; maintenance; power plant; boiler; failure cause; failure mode; maintenance cost; maintenance standard; criticality matrix.